The Long Noncoding RNA RPS10P2-AS1 Is Implicated in Autism Spectrum Disorder Risk and Modulates Gene Expression in Human Neuronal Progenitor Cells - Bilinovich, Stephanie M.; Lewis, Kristy; Grepo, Nicole; Campbell, Daniel B. (Frontiers in Genetics, 2019)
Most of the genetic risk for autism spectrum disorder (ASD) is inherited as common genetic variants, although some rare mutations have been identified in individuals with ASD. Common genetic variants are most parsimoniously identified by genome wide association studies. Genome wide association studies have identified several genetic loci with genome wide association with ASD. However, genome wide association studies only identify regions of the genome associated with phenotypic traits. Identification of the functional elements requires additional experimental evidence. Here, we demonstrate that a genome wide association study locus for ASD on chromosome 20p12.1, rs4141463, implicates a noncoding RNA as a functional element. Although rs4141463 lies within an intron of the protein-coding MACROD2 (MACRO domain containing 2) gene, expression of MACROD2 is neither altered in postmortem temporal cortex of individuals with ASD nor correlated with rs4141463 genotype. Our bioinformatics approaches revealed a noncoding RNA transcript near the autism susceptibility signal, RPS10P2-AS1 (ribosomal protein S10 pseudogene 2 anti-sense 1). In a panel of 15 human tissues, RPS10P2-AS1 was expressed at higher levels than the protein-coding MACROD2 in both fetal temporal cortex and adult peripheral blood. In postmortem temporal cortex, expression of RPS10P2-AS1 was increased 7-fold in individuals with ASD (P=0.02) and increased 8-fold in individuals with the ASD-associated rs4141463 genotype (P=0.01). Further, RPS10P2-AS1 expression was increased in human neural progenitor cells exposed to model air pollutants, indicating that both genetic and environmental factors that contribute to ASD increased RPS10P2-AS1 expression. Overexpression of RPS10P2-AS1 in human neural progenitor cells indicated substantial changes in neuronal gene expression. These data indicate that genome-wide significant associations with ASD implicate long noncoding RNAs. Because long noncoding RNAs are more abundant in human brain than protein-coding RNAs, this class of molecules is likely to contribute to ASD risk.